Analisis Kesesuaian dan Kelayakan Agrowisata pada Desa Penyangga Danau Rawa Pening - Al Faritsi, Adnin Maulana; Sutrisno, Alfred Jansen (JURNAL MANAJEMEN AGRIBISNIS (Journal Of Agribusiness Management); Vol 10 No 1 (2022): Jurnal Manajemen AgribisnisDO - 10.24843/JMA.2022.v10.i01.p06, 2022)
Utilization of the landscape of Rawa Pening Lake and its surroundings has not been optimized to the maximum. Where, residents of buffer village Lake Rawa Pening such as residents in Pojoksari Village, Bejalen Tambakboyo, and Asinan only use Rawa Pening Lake for sources of agricultural irrigation, aquaculture and water hyacinth cultivation. Whereas, the four villages can become agricultural-based tourism villages or agro-tourism villages. The objective of this study is to analyze the feasibility and suitability of the landscape of the four buffer villages into agrotourism villages. The methods used in this study are descriptive statistics, where there are 10 assessment criteria with each weight. Feasibility and suitability in each buffer village are assessed from aspects of feasibility are access, recreational resources, tourism facilities, tourism management and agrotourism programs and activities and then the suitability aspect are assessed from objects and attractions be it agricultural-based objects, natural objects, historical objects, and socio-cultural attractions. Based on the result of assessment, it was found that Bejalen Village and Asinan Village were very feasible and suitable villages to become agrotourism village, while for Tambakboyo Village it is quite feasible and suitable, then Pojoksari Village is a village that is less feasible and suitable of being an agrotourism village. So that of the four villages as buffer villages Lake Rawa Pening, only Bejalen and Asinan villages are the main priority for agrotourism development.